2008
DOI: 10.1007/s10658-008-9387-x
|View full text |Cite
|
Sign up to set email alerts
|

Host range and phytotoxicity of Stemphylium solani, causing leaf blight of garlic (Allium sativum) in China

Abstract: Since 2004, a new leaf blight disease on garlic of high severity has been observed in Dangyang County, Hubei province, China. Initial symptoms consisted of multiple, small, irregular to oval, white leaf spots, which enlarge to produce sunken purple lesions, sometimes surrounded by a bright yellow margin. As the disease progressed, lesions expanded and merged, resulting in withering of leaf tips. After isolation and pathogenicity testing, the causal agent of leaf blight of garlic was identified as Stemphylium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
(32 reference statements)
2
17
2
2
Order By: Relevance
“…Remarkable variations were also observed in conidial color of 24 isolates of S. vesicarium on PDA, where deep brown, brown and light brown color conidia were observed. The current findings were well supported by some reported works [17,19,21], which worked on Stemphylium solani and Stemphylium lycopersici and observed tan to light brown colored conidia. Koike et al [19] and Zheng et al [21] found brown colored conidia of Stemphylium botryosum and Stemphylium solani.…”
Section: Discussionsupporting
confidence: 91%
“…Remarkable variations were also observed in conidial color of 24 isolates of S. vesicarium on PDA, where deep brown, brown and light brown color conidia were observed. The current findings were well supported by some reported works [17,19,21], which worked on Stemphylium solani and Stemphylium lycopersici and observed tan to light brown colored conidia. Koike et al [19] and Zheng et al [21] found brown colored conidia of Stemphylium botryosum and Stemphylium solani.…”
Section: Discussionsupporting
confidence: 91%
“…Symptoms of the disease start as small white spots (1 to 3 mm) enlarging to elongated purple necrotic lesions along the vein, followed by blighting of the leaf tips. Similar symptoms were produced by culture filtrates of S. solani, and a strong correlation was also found between garlic cultivar sensitivity to S. solani and sensitivity to S. solani culture filtrates (29), suggesting the possible involvement of phytotoxins in lesion symptom development. We recently found that S. solani isolated from garlic produced toxins that were non-host-specific, and caused symptoms normally associated with leaf blight on a variety of plants (29).…”
supporting
confidence: 54%
“…We used ethyl acetate to extract the SS-toxin from culture filtrate. Variable phytotoxicity of different batches of culture filtrates was observed in this study, and this might be related to the age of cultures, since toxin production of S. solani isolates was reduced after transferring for several generations (29).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The symptoms of the disease initially consist of small white spots enlarging to elongated purple necrotic lesions along the vein followed by blighting of the leaf tips. The pathogen produces a non-host-specific toxin, SS-toxin, which is capable of causing symptoms normally associated with leaf blight (Zheng et al 2009). However, the chemical structure and precise mode of action of SS-toxin has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%